Hybrid Processes for Extraction–separation of Tocopherols from Crude Palm Oil - Vachiraanan, K.; Rattanapisit, J.; Sridang, P. (Journal of Applied Membrane Science & Technology, 2017)
The aim of this study was to evaluate the hybrid processes for extraction and separation of tocopherols from crude palm oil. The saponification method was used to extract crude palm oil under various concentrations of alcoholic KOH in the range of 10–60% w/v in a lab scale unit. The experiments were conducted at a temperature and saponification time in the range of 60–80°C and 20–40 min respectively. The performance and efficiency of ultrafiltration were investigated by filtering a fraction of unsponifiables. The results showed that the optimum condition of saponification was 10% alcoholic KOH with the minimum loss of α–tocopherol of around 19%. A lab scale filtration unit with a hydrophobic sheet membrane was operated under a frontal filtration mode at room temperature. The results pointed out that ultrafiltration could remove most of the residual triglycerides and phospholipids contained in unsponifiables at a TMP of 0.25–1.0 bars. The removal of up to 70% of triglycerides and phospholipids was reached when the mixture was ultrafiltered. In addition, these hydride processes present a one of the great option for α–tocopherol purification losing about 5% of yield.